The Effectiveness of Administrative Sanctions Against Environmental Pollution Cases in Indonesia - Khaidar, Naufal; Nurrahman, David Baniardy; Mubarak, Teunku Ahmad Zaki (Universitas Negeri Semarang, 2023)
This study investigates the effectiveness of administrative sanctions as a regulatory tool in combating environmental pollution cases in Indonesia. Despite the implementation of various environmental regulations and administrative penalties, the persistence of pollution incidents raises questions about the efficacy of these measures. Through a comprehensive review of legal frameworks, case studies, and empirical data, this research aims to assess the impact of administrative sanctions on deterring environmental violations and promoting compliance. Key factors influencing the effectiveness of administrative sanctions, including enforcement mechanisms, institutional capacity, public awareness, and stakeholder engagement, will be analyzed. Additionally, the study will examine challenges and opportunities for enhancing the enforcement of environmental regulations through administrative sanctions. By providing insights into the strengths and limitations of current regulatory approaches, this research seeks to inform policy recommendations for strengthening environmental governance and achieving sustainable development goals in Indonesia.